Effect Of Repeated Far Field Earthquake On The Ductility Demand Of Low-Rise Reinforced Concrete Buildings - Muhammad, Mohd Khairul Azuan (2011)
Impacts of seismic activity on building should be considered seriously to provide a safe building. Earthquake phenomenon is not a single event but repeated phenomenon. However, current seismic design codes are ignored the effects of repeated earthquake. During the earthquake hits the ground, the factor that directly related to the damage of the structure is well known as ductility demand. The objective of this study is to determine the effect of repeated earthquake on the ductility demand of low-rise RC buildings. The nonlinear time history analysis performed to determine the ductility demand for two low rise building models which is 3 storey and 6 storey using RUAUMOKO software. There are 20 pairs of far field earthquake (FFE) randomly combined was used to performed 1800 analyses. Findings from this study showed that, the repeated earthquake give the increment 14.91% and 48.69% of ductility demands for 3 and 6 storey models, respectively. Meanwhile, force reduction factor also give the increment 113.39% and 40.49% of ductility demand for 3 and 6 storey models, respectively.